RETRACTED: The Impact of the Use of Piped Water with Genesis Artifact On Electrocardiogram - Lesmana, Hendy (Universitas Aisyah Pringsewu, 2018)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Aisyah: Jurnal Ilmu Kesehatan to article entitled “The Impact of the Use of Piped Water with Genesis Artifact On Electrocardiogram” Vol 3, No 2, pp. 131-136, December 2018, DOI: http://doi.org/10.30604/jika.v3i2.110.This paper has been found to be in violation of the Jurnal Aisyah: Jurnal Ilmu Kesehatan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Medika Respati : Jurnal Ilmiah Kesehatan, Vol. 13, No. 1 (2018), pp. 30-37, entitled